Construction Contracts Without Deeds of Consolidation and Customary Land Compensation: Case Study Padang Sicincin Toll Project - Rahman, Fadhil; Azheri, Busyra; Fendri, Azmi (Faculty of Law, Andalas University, 2024)
The padang-sicincin toll road construction project in Indonesia aims to accelerate infrastructure development and improve regional connectivity in Sumatra. However, the project faces legal and social obstacles, particularly in land acquisition for the public interest on customary land. Customary land, owned by specific communities, often leads to conflicts due to differences in property rights and compensation. The land acquisition process can hamper project implementation and harm indigenous people. This study uses an empirical juridical approach, analyzing primary data from interviews, field situation data, and relevant laws and regulations. The research concludes that there is a need to improve the rules and stages of land acquisition related to customary law community areas and the maturation of national development program planning. Additionally, improved regulations and applications related to land acquisition must be completed before a construction work contract is made. This research can contribute to developing construction law and protecting customary land rights in Indonesia.